Xenodon Semicinctus (Ringed Hognose Snake): Aberrant Coloration - Tettamanti, Germán (2022)
X. semicinctus is a Dipsadidae snake with distribution in Argentina (Buenos Aires, Catamarca, Chubut, Córdoba, Entre Ríos, La Pampa, La Rioja, Mendoza, Neuquén, Río Negro, Salta, San Juan, San Luis, Santiago del Estero y Tucumán) and Bolivia (Williams et al. 2021. Revista Mus. La Plata 6: 98). This snake has a robust body, up to 600 mm long and with a wedge-shaped keel at the end of the snout; its normal dorsal coloration presents a pattern of 13 to 22 triads of incomplete black-red-black rings separated from each other by a yellowish ring (Scrocchi and Cruz 1993. Pap. Avul. Zool. 38 (10):171-185) (Fig. 1A). This species is semifossorial, with diurnal habits and with a preference for arid sandy environments (Vera and Tettamanti 2022. In Povedano [Ed.], Reptiles de Buenos Aires, pp. 104-105. La Biblioteca del Naturalista, Buenos Aires).On 22 January 2021 we observed a specimen of X. semicinctus with an aberrant color pattern on a shoulder of National Route 3 (39.232028°S 62.598139°W; WGS 84; 19 m elev.), in close to Mayor Buratovich town, Buenos Aires province, Argentina; it was moving over sand dunes covered by clumps of Sporobolus rigens and Senecio bergii.In this specimen (Fig. 1B) the transverse red bands are transformed into longitudinal stripes. This aberrant pattern has been reported in other species (Clause and Becker 2015. Herp. Notes. 8: 331-334), but this is the first time that has been reported for X. semicinctus.